2014
DOI: 10.1007/s00484-014-0932-3
|View full text |Cite
|
Sign up to set email alerts
|

Verification of impact of morning showering and mist sauna bathing on human physiological functions and work efficiency during the day

Abstract: Recently, a growing number in Japan are switching to taking baths in the morning (morning bathing). However, the effects of the morning bathing on human physiological functions and work efficiency have not yet been revealed. Then, we hypothesized that the effect of morning bathing on physiological functions would be different from those of night bathing. In this study, we measured the physiological functions and work efficiency during the day following the morning bathing (7:10–7:20) including showering, mist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
2
0
1
Order By: Relevance
“…In an earlier study, we found that a morning mist sauna was safe and that it maintains skin temperature compared to other bathing methods. We also found that the morning mist sauna bathing improves work efficiency compared to other bathing methods during the work day following the morning bathing [4]. In the present study, we verified that the morning showering and mist sauna were not effective improving from sleeping quality in this study.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In an earlier study, we found that a morning mist sauna was safe and that it maintains skin temperature compared to other bathing methods. We also found that the morning mist sauna bathing improves work efficiency compared to other bathing methods during the work day following the morning bathing [4]. In the present study, we verified that the morning showering and mist sauna were not effective improving from sleeping quality in this study.…”
Section: Discussionsupporting
confidence: 65%
“…We found that compared to other bathing methods, a morning mist sauna was safe and maintains the skin temperature. Moreover, it was found that morning mist sauna bathing improves work efficiency compared to other bathing methods during the day following the morning bathing [4]. However, the effects of morning bathing methods on people's sleep quality have not yet been revealed.…”
Section: Introductionmentioning
confidence: 99%
“…Również celem treningu jest osiągnięcie reakcji hormonalnej w organizmie człowieka, która w przypadku podniesienia poziomu endorfin wywołuje odpowiednie, zamierzone reakcje kliniczne. Zachowanie tych elementów bez wątpienia wspiera układ odpornościowy [5,6,7,8].…”
Section: Opis Stanu Wiedzyunclassified
“…A study published in International Journal of Biometeorology by Soomin Lee and colleagues concluded that the morning mist sauna has reduced burden on cardiovascular system and that skin temperature was maintained compared to other bathing methods and that it improves the work efficiency during the task period of the day [16]. Sathoshi Iwase et al [17] concluded that mist sauna is safer sauna bathing system which has more efficiency on circulatory and thermoregulatory function when compared to dry sauna bathing.…”
Section: Introductionmentioning
confidence: 99%